A comparative study of Tetum prepositions and Makasae postpositions - Soares, Antonio Constantino (Abdul Media Literasi, 2025)
This study examines the syntactic roles of prepositions in Tetum and postpositions in Makasae, with a focus on their functions in conveying spatial and relational concepts. Tetum, an Austronesian language spoken in East Timor, and Makasae, a Trans-New Guinea language spoken in Timor-Leste's eastern districts, employ different syntactic structures for conveying relationships between noun phrases and other sentence elements. While Tetum uses prepositions such as